Stress intensity factor for bonded dissimilar materials weakened by multiple cracks - Hamzah, K.; Nik Long, N. M. A.; Senu, N.; Eshkuvatov, Z. K. (Elsevier, 2020)
The new hypersingular integral equations (HSIEs) for the multiple cracks problems in both upper and lower parts of the bonded dissimilar materials are formulated using the modified complex potential method, and with the help of the continuity conditions of the resultant force function and displacement. The crack opening displacement is the unknown and the traction along the crack as the right term of the equations. The appropriate quadrature formulas are used in solving the obtained HSIEs for the unknown coefficients. Numerical results for the multiple inclined or circular arc cracks subjected to the remote shear stress are presented.